The Digitalization Phenomenon in the Yogyakarta Omah Cangkem (OCM) and the 4 Suku Menanti Community in Bengkulu - Dhanurseto Hadiprashada; Kundori Kundori (Sekolah Tinggi Multi Media, 2025)
Behind the improvement brought by digital media, various challenges have also emerged. Phenomena such as the spread of fake news (hoaxes), digital privacy, and societal polarization have become issues that often arise along with the rapid growth of this media. This study aims to discuss the digitalization of community works and products in the development of tourist villages in DI. Yogyakarta and Bengkulu Province. The research method used is a qualitative approach with data collection techniques through in-depth interviews, participatory observation, and focus group discussions. Research informants include stakeholders related to the development of tourist villages, community leaders, and related local government officials. Data were analyzed using a thematic approach. This study found that the increase in documentation of cultural activities (works) and community products in the form of audio visuals (digital) in the development of tourist villages continues to be carried out. The process of developing a tourism village is carried out by effectively digitizing works and products by the surrounding community. The effectiveness of the activities carried out by each community has an impact on the development of existing tourism villages. This is what then gave rise to the integration of community-based tourism village development models.